The Effect of Price, Product Quality, and Brand Image on The Originote Skincare Product Purchase Decision - Ernawati Ohoitenan; Muhammad Arief; Primasatria Edastama (International Publisher (YAPENBI), 2025)
This study examines the effect of price, product quality, and brand image on purchasing decisions for The Originote skincare products in Bekasi City. Using a non-experimental quantitative approach and descriptive design, data were obtained from 105 respondents through an online survey with Google Forms. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results showed that product quality did not have a significant effect on purchasing decisions for The Originote skincare products , but price and brand image had a significant effect. The price of The Originote products is considered affordable and in accordance with consumer desires, while The Originote's brand image is well-known and easy to remember by consumers. Consumer attitudes can also be influenced by external factors such as changes in needs or economic conditions that cannot be fully controlled in this study. These findings provide important insights for marketers in developing effective marketing strategies for skincare products.